ROLE OF MAGNETIC RESONANCE IMAGING IN THE EVALUATION OF POSTERIOR CRANIAL FOSSA SPACE-OCCUPYING LESIONS - SABINA SHAMS; BASER SC; RUMANA HITAWALA (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The current study was conducted with the objective to evaluate and characterize various posterior cranial fossa space-occupying lesions as solid, cystic, vascular, and infective. The current study aims to evaluate this and to help clinicians with early detection, exact site, and extent of the lesion. Methods: A Cross-sectional study was conducted over a period of 18 months (January 2021 to June 2022) in patients who were clinically suspected and who underwent magnetic resonance imaging to evaluate posterior fossa space-occupying lesions at Geetanjali Medical College and Hospital, Udaipur. Results: In our study, the most common posterior fossa space-occupying lesion was acoustic neuroma (12, 2l.82%) followed by arachnoid cyst (7, 12.73%). The most common space-occupying lesion in female patients was acoustic neuroma (7 patients, 30.43%) whereas in male patients, the most common space-occupying lesion was arachnoid cyst (6, 18.75%). There were almost equal numbers of intra (49.09%) and extra-axial cases (50.91%). Conclusion: Due to the restricted space, involvement of the crucial brain stem nuclei, and fourth ventricle, posterior fossa space-occupying lesions are regarded as critical brain lesions. Early diagnosis and treatment are now possible thanks to modern diagnostic and therapeutic modalities.